The Influence of Taste, Packaging and Price on Purchasing Decisions of Pie Ngalam Heritage Products, Malang, East Java - Yoga, Tirta; Khoirunnisa, Ninin (Kadiri University - Faculty of Agriculture, 2025)
Business competition is increasingly intense, requiring companies to adapt to the evolving competitive dynamics to remain viable. Producers must highlight the uniqueness and quality of their products to influence consumer purchasing decisions. Pie Ngalam Heritage is a manufacturer specializing in producing pie cakes designed as keepsakes from Malang. Pie Ngalam products possess distinct qualities that help them sustain a competitive advantage in the market. This study aims to evaluate the influence of taste, packaging, and price on consumer purchasing decisions regarding Pie Ngalam Heritage products in Malang. The study comprised a cohort of 50 consumers engaged in numerous transactions and analyzed the data. We analyzed data using structural equation modeling (SEM) and the SEM WarpPLS technique. In particular, we employed the hierarchical component model (HCM) or second-order method. Evaluated the strength and reliability of the relationship between hidden variables and their indicators. The findings revealed that flavor positively and significantly impacted purchasing decisions, with a t value of 2.234, which exceeds the critical value of 2.010. While packaging also had a positive effect, its impact was not statistically significant, as shown by a low t-value of 1.444, below the critical value of 1.677. Conversely, price had a substantial and positive effect on purchasing decisions for Pie Ngalam Heritage products, with a strong statistical significance indicated by a t value of 4.838, well above the critical value of 2.406. To boost sales at Pie Ngalam Heritage, businesses should focus more on affordable pricing and superior taste rather than making significant investments in packaging.